Criminal Law Policy in Implementing, Values of Justice and Legal Certainty (Case Study of Defamation) - Iren Br Bangun; Purba, Desriani Ronay Fiona; PA, Eh Bungana Beru; Ibrahim, Maulana (PT FORMOSA CENDEKIA GLOBAL, 2023)
Globalization, which began in the early 20th century, was marked by revolutions in transportation and electronics, expanding and accelerating trade between countries. The impact is significant, especially in the field of multimedia companies which are competing to dominate the global mass media market. Technology plays a central role in this global phenomenon, turning the world into a global village. A case study of defamation via Facebook in Pandahan Village, South Kalimantan, is the focus of this research. Analysis of material criminal law based on the law is applied in the decision of the Pli District Court. Meanwhile, the Micro, Small and Medium Enterprises (MSME) sector in Indonesia is an important factor in supporting the economy and local economic growth. Through a literature study, this study investigates the application of material criminal law in cases of defamation in cyberspace and explores the potential of MSMEs as drivers of the local economy. It is hoped that the results of this research can provide further insight into the challenges and opportunities faced by society and the government in facing the phenomena of globalization, technology and local economic development.